Comparative study between knot suturing versus Titanium endoclip during laparoscopic appendectomy stump closure in non complicated appendicitis - Ahmed Shadad Abdelwahed; Ahmed Mahmoud Hussien; Mostafa Abdelhameed Soliman; Nader Makram Milad (Cairo : Ahmed Shadad Abdelwahed, 2016)
Purpose: The goal of the study was to compare strength, healing, and inflammation of appendiceal stumps closed by ligatures using polyglactin (Vicryl) Versus endoclips during laparoscopic appendectomy in a specific group of patients with uncomplicated appendicitis. Methods: Between October 2012 to October 2014 , fifty patients were prospectively randomized into two groups (25 females & 25 males), who had their appendiceal stump secured by metal endoclips (Group 1) and endoloop (Group 2). Results: Operative time was longer in the endoloop group and it was found to be of important statistically significance with P-values 0.044. No statistically significant differences were detected between the two groups in terms of intraoperative complications, amount of blood loss, operative bowel complications or hospital stay. There were no operative complications directly attributable to stump closure. The follow-up time was two months, with no readmissions of any patients of the two groups.Conclusions: The closure of the appendiceal stump by endoclipping during laparoscopic appendectomy in uncomplicated appendicitis is safe, easy application, the time was shorter and a simpler alternative in comparison with the use of an endoloop
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: Acute appendicitis; Appendicular stump; Laparoscopic appendectomy